2015
DOI: 10.1073/pnas.1511711112
|View full text |Cite
|
Sign up to set email alerts
|

Opposing roles of STAT1 and STAT3 in IL-21 function in CD4 + T cells

Abstract: IL-21 is a type I cytokine essential for immune cell differentiation and function. Although IL-21 can activate several STAT family transcription factors, previous studies focused mainly on the role of STAT3 in IL-21 signaling. Here, we investigated the role of STAT1 and show that STAT1 and STAT3 have at least partially opposing roles in IL-21 signaling in CD4 + T cells. IL-21 induced STAT1 phosphorylation, and this was augmented in Stat3-deficient CD4 + T cells. RNA-Seq analysis of CD4 + T cells from Stat1-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
91
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(97 citation statements)
references
References 36 publications
6
91
0
Order By: Relevance
“…IL-6 had been shown activating the STAT3/RORγt signaling pathway, which can induce Th17 cells secreting IL-6, IL-17 and other cytokines 8. Previous studies confirmed that ROR γ t is an indispensable specific transcription factor for IL-17A synthesis in Th17 cells 9,16. The above results of our study indicated that STAT3/ROR signaling pathway was obviously inhibited.…”
Section: Discussionsupporting
confidence: 64%
“…IL-6 had been shown activating the STAT3/RORγt signaling pathway, which can induce Th17 cells secreting IL-6, IL-17 and other cytokines 8. Previous studies confirmed that ROR γ t is an indispensable specific transcription factor for IL-17A synthesis in Th17 cells 9,16. The above results of our study indicated that STAT3/ROR signaling pathway was obviously inhibited.…”
Section: Discussionsupporting
confidence: 64%
“…The activation of the JAK-STAT signaling pathway by IL-21 has been extensively studied in this [44]. JAK3 and STAT3 are the key proteins in the JAK-STAT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…STAT1 and STAT3 have partially opposing roles in IL-21 signaling. RNA-sequence analysis showed that STAT1 and STAT3 are critical for IL-21-mediated gene regulation, including Tbx21 and interferon γ (32). Notably, IL-21-induced expression of suppressor of cytokine signaling 3 (Socs3) and Socs1 are decreased in Stat3 -/-cells (33).…”
Section: Signaling By Il-21mentioning
confidence: 99%